Clinical and molecular delineation of Tetrasomy 9p syndrome: Report of 12 new cases and literature review. (2nd April 2015) - El Khattabi, Laïla; Jaillard, Sylvie; Andrieux, Joris; Pasquier, Laurent; Perrin, Laurence; Capri, Yline; Benmansour, Abdelmadjid; Toutain, Annick; Marcorelles, Pascale; Vincent‐Delorme, Catherine; Journel, Hubert; Henry, Catherine; et al.
Abstract : Tetrasomy 9p is a generic term describing the presence of a supernumerary chromosome incorporating two copies of the 9p arm. Two varieties exist: isodicentric chromosome 9p (i(9p)), where the two 9p arms are linked by a single centromeric region, and pseudodicentric 9p (idic(9p)), where one active and one inactive centromere are linked together by a proximal segment of 9q that may incorporate euchromatic material. In living patients, i(9p) and idic(9p) are usually present in a mosaic state. Fifty‐four cases, including fetuses, have been reported, of which only two have been molecularly characterized using array‐CGH. Tetrasomy 9p leads to a variable phenotype ranging from multiple congenital anomalies with severe intellectual disability and growth delay to subnormal cognitive and physical developments. Hypertelorism, abnormal ears, microretrognathia and bulbous nose are the most common dysmorphic traits. Microcephaly, growth retardation, joint dislocation, scoliosis, cardiac and renal anomalies were reported in several cases. Those physical anomalies are often, but not universally, accompanied by intellectual disability. The most recurrent breakpoints, defined by conventional cytogenetics, are 9p10, 9q12 and 9q13. We report on 12 new patients with tetrasomy 9p (3 i(9p), 8 idic(9p) and one structurally uncharacterized), including the first case of parental germline mosaicism. All rearrangements have been characterized by DNA microarray. Based on our results and a review of the literature, we further delineate the prenatal and postnatal clinical spectrum of this imbalance. Our results show poor genotype‐phenotype correlations and underline the need of precise molecular characterization of the supernumerary marker. © 2015 Wiley Periodicals, Inc.